Biopsychosocial Factors in Children Referred With Failure to Thrive: Modern Characterization for Multidisciplinary Care - Nina Mazze MD, JD, HBSc; Emma Cory MD; Julie Gardner RN; Mara Alexanian-Farr MSc, RD; Carly Mutch OT; Sherna Marcus OT; Julie Johnstone MD, MScCH; Meta van den Heuvel MD, PhD (SAGE Publishing, 2019)
The objective of this study was to characterize biopsychosocial characteristics in children with failure to thrive with a focus on 4 domains: medical, nutrition, feeding skills, and psychosocial characteristics. A retrospective cross-sectional chart review was conducted of children assessed at the Infant and Toddler Growth and Feeding Clinic from 2015 to 2016. Descriptive statistics were used to analyze the data. One hundred thirty-eight children, 53.6% male, mean age 16.9 months (SD = 10.8), were included. Approximately one quarter of the children had complex medical conditions, medical comorbidities, and developmental delays. The mean weight-for-age percentile was 15.5 (SD = 23.9), and mean weight-for-length z score was −1.51 (SD = 1.4). A total of 22.5% of children had delayed oral-motor skills and 28.3% had oral aversion symptoms. Caregiver feeding strategies included force feeding (14.5%) and the use of distractions (47.1%). The multifactorial assessment of failure to thrive according to the 4 domains allowed for a better understanding of contributing factors and could facilitate multidisciplinary collaboration.